2005
DOI: 10.1111/j.1740-8261.2005.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Assessment of Body Fat in Beagles

Abstract: Obesity is the most common nutritional disorder in small animals. To establish a computed tomographic (CT) method for assessment of visceral and subcutaneous fat content in the dog, CT analysis was performed in normal and obese beagles. Fat area was measured by the level detection method at varied attenuation ranges and compared with body fat content estimated by the deuterium oxide dilution method. Fat area measured at L3 using the attenuation range of -135/-105 Hounsfield unit had the best correlation with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 4 publications
6
68
1
3
Order By: Relevance
“…Specifically, the CVs were 0.25%, 1.19%, 0.42%, and 3.08% for TAT, VAT, LT and CB respectively. The CVs for TAT, VAT and LT compare favorably with recently reported CVs of human 3T FWMRI measurements of the same quantities (14,15).…”
Section: Resultssupporting
confidence: 71%
“…Specifically, the CVs were 0.25%, 1.19%, 0.42%, and 3.08% for TAT, VAT, LT and CB respectively. The CVs for TAT, VAT and LT compare favorably with recently reported CVs of human 3T FWMRI measurements of the same quantities (14,15).…”
Section: Resultssupporting
confidence: 71%
“…Neutering via surgical removal of the testes or ovaries in dogs and cats is known empirically to increase the risk of obesity [7, 11, 18]. It has been found that if dogs and cats exceed their ideal body weight by 15%, the harmful physical effects associated with obesity, including heart disease, exacerbation of joint disease and diabetes, become apparent [4, 18].…”
mentioning
confidence: 99%
“…We therefore designated the CT attenuation range indicating areas of fat in humans to select areas of fat. The CT cross-sectional images evaluated in this study were selected from the past studies done [11]. We selected areas from the thoracic (T6, T9 and T12) and lumbar spines (L3 and L5).…”
mentioning
confidence: 99%
“…In the human medical practice, computed tomography (CT) is one of the most advanced methods for the accurate assessment of intraabdominal fat accumulation (Hirooka et al, 2005). Although the CT method using a single image at vertebrae L3-5 is a useful technique for the evaluation of canine obesity and body fat distribution, an accurate procedure has been developed for a single breed (the Beagle) only (Ishioka et al, 2005a).…”
Section: Abstract: Leptin Insulin Resistance Abdominal Fat Computmentioning
confidence: 99%
“…The dogs were subjected to general anaesthesia for the procedure. Subcutaneous and visceral fat areas were measured on a crosssectional scan (120 Kv, 30 mA, 5 mm slice thickness) at the level of the L2 and L3 vertebrae (Ishioka et al, 2005a). The pixels with attenuation values in the selected range were depicted as red (Fig 1).…”
Section: Computed Tomographymentioning
confidence: 99%